LU(S)TI in the global South: an empirical analysis of land use and socio-economic transport interaction in Tanzania using mobile network data - Engelmann, Gregor (2021)
The majority of rural-urban migration is filtered through slums: informally established, unplanned, and unrecognised by the government, scientists have a minimal understand- ing of the 200,000 that exist worldwide, never mind enough insight into the millions of individuals living there. This limited understanding often coincides with a more general absence of data in traditional urban planning approaches, leading to most cities seeing development, positive or otherwise, preceding planning.